Analysis of Prospects for Sustainable Land use (Lands of Agricultural Designation) in the Republic of Kazakhstan in the Context of the Development of Alternative Energy - Omarbekova, Ardak Dikhanbayevna; Pentayev, Toleubek Pentayevich; Igembayeva, Ainur Kanatovna; Abayeva, Kurmangul Toletaevna (International Journal of Energy Economics and Policy, 2017)
The main purpose of this paper is to identify the promising directions of arable areas use of the Republic of Kazakhstan. The authors present a methodology for calculating the integral index which is based on a system of quantitative indicators reflecting the use of agricultural land and efficiency of agricultural production. Using these methodologies, the authors conducted a comprehensive evaluation of sustainable land use in the regions of the Republic of Kazakhstan. The results of the study allow the authors to conclude that the arable areas are used inefficiently. An important reserve for increasing the efficiency of agriculture can become an alternative energy. The specific interest is the development of bio-energy as a promising tool for sustainable development of the agricultural sector. Keywords: land resources, sustainable land management, alternative energy, inexhaustible energy sources (IES), bioenergy, biological fuel JEL Classifications: R14, R52, Q10